The impact of education level and economic freedom on gender inequality: panel evidence from emerging markets - Tokal, Pinar; Sart, Gamze; Danilina, Marina; Ta’Amnha, Mohammad A. (Frontiers in Psychology, 2023)
Gender inequality is a critical factor for all ingredients of a healthy society and sustainable development. Therefore, measures to decrease the gender inequalities in economic, social, and political life are important for economic and social development of a society. This study analyzes the influence of education level and economic freedom on gender inequality in emerging markets over the 2000-2020 term through causality and cointegration tests. The results of the causality test uncover a bidirectional causality between education level, economic freedom, and gender inequality. In other words, there exists a mutual interaction among education level, economic freedom, and gender inequality in the short run. Furthermore, the findings of cointegration analysis indicate that education level and economic freedom have a negative impact on gender inequality in the long run, but the education level is much more effective on gender inequality than that of economic freedom nearly in all emerging markets.